Pandawara Group sebagai Gerakan Ecomedia: Analisis dari Perspektif Ekologi Politik - Subangkit, Sapta Hari; Azwar, Azwar; Intyaswati, Drina (Mahesa Research Center, 2025)
This study analyzes the Pandawara Group’s social movement via sosial media from an ecomedia and political ecology perspective. The focus is on examining how this movement emerged and operates within the landscape of power, economy, and media, as well as how the group utilizes social media to communicate environmental issues and mobilize public participation. This qualitative research employs ecomedia theory, specifically the political ecology perspective as explained by Lopez (2024), which encompasses aspects of creation, function, audience, media ecosystem, and funding sources. Data was collected through literature studies, observation, and documentation of the Pandawara Group's digital assets. The findings show that the Pandawara Group is an ecomedia social movement that was created organically in response to environmental pollution. Its goal is to raise awareness, and it has successfully mobilized public participation through social media. The movement operates within the dynamics of political ecology by interacting with various actors and utilizing diverse funding sources, including sponsorships. In conclusion, the Pandawara Group demonstrates how a social movement can leverage ecomedia and operate within the dynamics of political ecology to address environmental issues.